Livestock production in central Mali: Attempts to produce raw materials of animal origin for the French textile industry during the colonial period - Wilson, R.T. (Informa UK Limited, 1981)
Outlines past attempts to develop a base of raw materials for the textile industry from indigenous animals in Mali. Describes notable efforts to upgrade local Macina sheep for increased wool production by selection or cross-breeding with Merinos, increasing goat wool production by crossing imported Angora goats with locals and increasing pelt production by crossing the local long-haired Black Moor sheep with Karakul (Bokhara) sheep. Causes of the failure discussed.